Property Rights Institutions and Investment - Saleh, Jahangir (World Bank, Washington, D.C., 2013)
This paper examines the channels through which alternative property rights institutions affect investment. These institutions are defined by a society's enforced laws, regulations, governance mechanisms and norms concerning the use of resources. A transaction cost framework is used to analyze the incentive impact of various types of property rights, liability rules, and rules regarding contracts. This framework is used to discuss the legal and cultural conditions necessary for the formation of productivity-enhancing organizations and the proper role of government in providing the infrastructure for private investment. A brief section examines the role of cultural and religious norms in determining the economic effectiveness of legal systems, with a focus on Islamic countries. The final section evaluates empirical approaches used to discover the specific ways property rights structures affect investment and growth.